Assessing the Service Quality Attributes Affecting the Satisfaction of the Northern Railway Passengers: An Empirical Study. Issue 1 (June 2020) - 'Ranjan', Rajeev Kumar; Thapar, Nitin; Siddiqui, Shoaib Alam; Painoli, Arun Kant
The present study aims to assess the intangible attributes of the service that have an impact on customer satisfaction. The Intangible attributes attached to the service, are difficult to determine. The Indian Railway network is one of the largest railway networks in the world. It is spread over 115, 000 km having 21, 617 passenger trains carrying 23 million passengers every day. In terms of revenue generation, it is a major contributor to the Indian economy but even then, the service level is very poor as compared to the other parts of the world. Due to increased competition in the modes of transportation, the Service attributes of Indian Railway acts as a strong influencer on Passenger Satisfaction. Indian Railways has a huge potential in terms of economic benefits if their service quality is improved. Various studies have tried to identify the important attributes regarding the Service Quality of Indian Railway. The SERVQUAL model provided important insights into the service attributes. The study attempts to identify the gap that exists in the service level, that is, service offered by the Indian Railway and expectation of the customers. In the study, only internal aspects like facilities (attributes) which make the journey comfortable and the absence of these attributes makes the passengers' journey uncomfortable are included. The result indicates that there exists a considerable gap in Reliability and Assurance dimensions of Railway service quality and the most important factors determining satisfaction of passengers are basic facilities, safety and security, cleanliness and employee behaviour towards passengers.